Shedding a light on ultraviolet-C technologies in the hospital environment - Demeersseman, N.; Saegeman, V.; Cossey, V.; Devriese, H.; Schuermans, A. (The Journal of hospital infection, 2023)
Ultraviolet (UV)-C light for disinfection has experienced a surge in popularity since the outbreak of COVID-19. Currently, many different UV-C systems, with varied properties that impact disinfection performance, are available on the market. Therefore this review aims to bundle the available information on UV-C disinfection to obtain an overview of its advantages, disadvantages, and performance-influencing parameters. A literature search was performed using the snowball search method in Google Scholar and PubMed with the following keywords: UV-C disinfection, UV-C dose, UV-C light source, UV-C repair mechanism, UV-C photoreactivation, and UV-C disinfection standards. The main parameters of UV-C disinfection are wavelength, dose, relative humidity, and temperature. There is no consensus about their optimal values, but, in general, light at a high dose and a spectrum of wavelengths containing 260 nm is preferred in an environment at room temperature with low relative humidity. This light can be generated by mercury-vapour, light-emitting diode (LED), pulsed-xenon, or excimer lamps. Multiple factors are detrimental to disinfection performance such as shadowing, a rough surface topography, a high level of contamination, repair mechanisms, and the lack of standardization. Also, there are health and safety risks associated with the UV-C technology when used in the proximity of people. UV-C disinfection systems have promising features and the potential to improve in the future. However, clarifications surrounding the different parameters influencing the technologies' effectiveness in hospital environment are needed. Therefore UV-C disinfection should currently be considered for low-level rather than high-level disinfection.